Kratom (Mitragyna speciosa Korth): Manfaat, Efek Samping dan Legalitas - Raini, Mariana (Media Penelitian dan Pengembangan Kesehatan, 2017)
Kratom or Mitragyna speciosa Korth (Rubiaceae) is tree that is commonly found in Southeast Asia. It has been considered useful as a herbal medication to treat a number of problems such as diarrhea, in the alleviation of pain, coughs, hypertension, and to improve sexual performance. The ingestion of kratom produces a stimulant effect at low dosages and an opioid-like effect at medium to high dosages. Kratom is often misused and easily purchased from the internet. The aim of this study is to review kratom from national and international journal, therefore, it can give the information for people and relevant institution related to the use, side effects and legality of kratom. the result of this study showed that the use of kratom regularly or over a period of time could lead to dependence and addiction. The users had tried to stop using kratom as they developed withdrawal symptoms.The symptoms of withdrawal included anorexia, weight lost, decreased sexual drive, insomnia, muscle spasms and pain, aching in the muscles and bones, watery eyes/nose, hot flushes, fever, decreased appetite, diarrhea, hallucination, delusion, mental confusion, emotional disturbance, insomnia. United Nations Office on Drugs and Crime (UNODC) has classified kratom as a New Psychoactive Substances (NPS). Indonesia allows the consumption, plant and trade of kratom. it can be concluded that ratom has a narcotic-like effect and it can cause dependence and addiction. The government should ban the use, planting and distribution of kratom.AbstrakKratom atau Mitragyna speciosa Korth (Rubiaceae) merupakan tanaman yang sering dijumpai di Asia Tenggara. Tanaman ini dimanfaatkan dalam pengobatan herbal untuk mengobati beberapa penyakit seperti diare, pereda nyeri, batuk, hipertensi, dan lemah syahwat. Mengonsumsi kratom dapat memberikan efek stimulan pada dosis rendah dan efek seperti opiat pada dosis menengah hingga tinggi. Kratom sering disalahgunakan dan mudah diperoleh melalui internet. Artikel ini bertujuan untuk mengkaji tanaman kratom sehingga dapat memberikan informasi kepada masyarakat dan instansi terkait tentang manfaat, efek samping, dan legalitas penggunaan kratom. Metode yang digunakan adalah dengan mengkaji dan menganalisis artikel kratom dari jurnal nasional dan internasional. Hasil kajian menunjukkan penggunaan kratom secara rutin atau dalam suatu periode dapat menimbulkan adiksi dan ketergantungan. Pengguna yang mencoba menghentikan penggunaan kratom dapat menyebabkan gejala putus obat. Gejala putus obat diantaranya anoreksia, nyeri dan kejang otot, nyeri pada tulang dan sendi, mata/hidung berair, rasa panas, demam, nafsu makan turun, diare, halusinasi, delusion, mental confusion, gangguan emosional, dan insomnia. United Nations Office on Drugs and Crime (UNODC) telah memasukkan kratom ke dalam New Psychoactive Products (NPS). Indonesia mengizinkan mengonsumsi, menumbuhkan, dan memperdagangkan kratom. Kesimpulannya adalah kratom mempunyai efek seperti narkotika dan dapat menimbulkan adiksi. Pemerintah sudah selayaknya melarang penggunaan, penanaman, dan peredaran kratom.